1982
DOI: 10.1139/v82-242
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of the singlet and triplet state of benzene by halogenated alkanes in the vapor phase

Abstract: . 60, 1767 (1982).The second order rateconstants (k,) for the quenching of the singlet state of benzene by several halogenated alkanes (viz. CH,Br2, CCI,, CH3CC13, CHCI,, CHF,, CH,CI, CH3F, CH2F2, CH2C12, CFCI,, CF2CI2, CF,CI, CF,) in the vapor phase have been measured. For CCl,, CHCI,, CH2C12, and CH,CI, which were previously studied by Das Gupta and Phillips, there is satisfactory agreement between the k, values obtained in the separate investigations. The linear dependence of the electron affinity of quench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…In the case of benzene and a large number of halocarbons it Finally, if full electron-transfer from excited aromatic to has been shown that In k, does indeed vary linearly with EAA, quencher occurs, the maximum slope should be l/RT -39 all the other terms of eq. [6] being constant. In the present case eV-I.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In the case of benzene and a large number of halocarbons it Finally, if full electron-transfer from excited aromatic to has been shown that In k, does indeed vary linearly with EAA, quencher occurs, the maximum slope should be l/RT -39 all the other terms of eq. [6] being constant. In the present case eV-I.…”
Section: Resultsmentioning
confidence: 96%
“…The charge transfer exciplex model of quenching is based on ketones (4) [5] In k, = ---+ In k2 RT [6] In k, x l -( l P~ -EAA -E s~ -C -P)I/RT possible to test eq. [6] by plotting In k, vs. lPD; the results of this plot are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that polar solvents increase this quenching (22,23). In a previous publication we reported on the fluorescence quenching of benzene vapour by a number of halocarbons (6). We report here on the effect of solvent polarity on this reaction in liquid phase and on the rates of quenching by CCl,, CH,CN, CHCl,, and CH3CCl, in solid phase.…”
Section: Introductionmentioning
confidence: 79%
“…Some exciplexes exhibit fluorescence which is characterized by a red-shift with respect to the uncomplexed excited monomeric state, a lack of vibronic structure, and different decay characteristics. Nonemissive exciplexes have also been shown to exist (2)(3)(4)(5)(6). In such cases, indirect evidence is obtained for the intermediacy of exciplexes.…”
Section: Introductionmentioning
confidence: 99%